PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA KARYAWAN BNI SYARIAH CABANG BANDUNG - Suherman, Usep Deden (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2018)
The purpose of this study was to determine education, training, employeeperformance and the influence of education and training on employee performance both partially and simultaneously. The research method used is descriptive method for 70 employees. The sampling technique used is simple random sampling. Meanwhile, the technique used to test the hypothesis is Path Analysis. The results of the study illustrate that education is in a sufficient category that can be seen in terms of decision making skills, interpersonal skills, job knowledge, organization knowledge, general knowledge and specific individual needs. When viewed from the training, it is generally in asufficient category that can be seen in terms of skills, knowledge, behavior. Judging fromthe performance of employees, in general, it is in the quite category also in terms of quality of work, timeliness, initiative, capability, and communication. Furthermore, the results of the study indicate that education and training have a positive and significant influence both partially and simultaneously on employee performance